ANALISIS PENGEMBANGAN KARIR KARYAWAN PADA PT. ASURANSI KREDIT INDONESIA ( ASKRINDO ) CABANG SAMARINDA KALIMANTAN TIMUR - Wahyu Rhomadhan (OBOR: Oikonomia Borneo, 2019)
The purpose of this study was to determine the suitability of career development provided by PT. Indonesian Credit Insurance (ASKRINDO) Samarinda Branch to its employees on Veithzal Rivai's theory of career development. This research method uses descriptive qualitative method. From the results of the study it was found that: (1) The stages of employee career development at PT. Indonesian Credit Insurance (ASKRINDO) Samarinda Branch in accordance with the stages proposed by Veithzal Rivai, namely the initial phase, the continuation phase, the maintenance phase and the retirement phase. (2) All employee data used for analysis shows that they have gone through 4 phases, namely the initial phase, the continuation phase, the retaining phase and the retirement phase.